Analysis of the Application of Signal in Motor Vehicle Tax Payment at UPT Samsat Bangkinang - M. Junaidi; Zulher; Abshor Marantika (LP2M IAIN Palopo, 2025)
This study analyzes the implementation of the SIGNAL (National Digital Samsat) application for Motor Vehicle Tax (PKB) payments at the UPT Samsat Bangkinang. Using a descriptive qualitative method with SWOT analysis, the research identifies internal and external factors. The results show that the strategic position lies in Quadrant II (WO Strategy), indicating significant opportunities amid internal weaknesses. The main strength is practicality and efficiency, supported by the Indonesian National Police (Korlantas). However, notable weaknesses include limited socialization budgets, lack of trained human resources, and insufficient digital promotion. Opportunities arise from the growing trend of digitalization in public services. The recommended WO strategy focuses on allocating funds for socialization, improving human resource capacity through training, and optimizing social media for public education. These efforts are expected to enhance the effectiveness of SIGNAL implementation and increase taxpayer participation in online services.